Polya Steps for Analyzing Errors in Mathematical Problem Solving - Suharti Suharti; Fitriani Nur; Bahrul Alim (AL-ISHLAH: Jurnal Pendidikan, 2021)
This research aims to ascertain the proportion of mistakes made by students while solving comparative and social arithmetic problems. This study falls under the category of qualitative descriptive research. Twenty-six students from class VII.6 were used as study participants. Data were gathered via interviews and administering exams. The analytical framework was derived from Polya's classification of errors. The findings of this research show that type of mistake. According to this research, mistakes in evaluating responses (fourth phase) are more prevalent than other types of errors. The fourth phase received a score of 43,8%, whereas the first phase received a score of 34,9%, the second phase received a score of 35,4%, and the third phase received a score of 36,5%. The mistakes in the first and second phases are indicative of fundamental and conceptual problems. The third level demonstrates mistakes in the processes and algorithms, followed by faults in confirming the solutions. The consequence of this study is the identification of pictures of mistakes made while answering comparison questions and social arithmetic, allowing for the development of more effective learning methods for future learning.